“La docencia y las comunidades de aprendizaje” - Casa Masabanda, Erika Paola (2023)
Currently, education has undergone educational transformations, where it is needed teachers that are constantly maintained updating in the pedagogical scopes, by achieving, what the relationship between the teacher and the learning community with a harmonious work environment to perform a good role. Faced to this, it has been shown, what teachers do not participate into collaborative activities, that is, which they predominate individualism, so it must aim collective participation at the learning communities’ structure for the strengthening their professional competence. This sense, the current project aim allows to be involved the teacher in the learning community, through collaborative activities for the teaching-learning process strengthening in the “Vicente León” Educational Unit from Latacunga Canton in the 2022-2023 academic period. The used methodology in the project is delimited qualitative research, by means the stages: preparatory, field work, analytical and informative. The method was inductive, because it was analyzed from particular to general, the teacher characteristics in the learning communities. The used technique was the interview with its instrument the interview guide addressed to authorities and teachers to get information about teamwork among teachers. The result was based on the reflection about the collaborative skills, what demand teacher for expanding their knowledge, from collaboration and cooperation and they are sensed safe to share their experience with other professionals, since their collective contribution is oriented at improving their professional performance. By contrasting the information, it was set, what teachers need for improving teamwork and being constantly updating for the strengthening their professional skills. For this reason, this research contributes with the workshops proposed methodological guide aimed at teamwork, it oriented to the learning communities for teachers, towards the education professional’s collaboration development, for responding to the changes, which demand by actual society with a continuous training vision, in order to improve the educational and professional process oriented to the knowledge production.